The effects of the invasive plants on soil nematodes vary with the duration of elevated CO2 treatment - Xiu-Rong Lu; Ming-Chao Liu; Wei-Wei Feng; Bo Qu; Jing-Kuan Wang; Yu-Long Feng (Plant Diversity)
Exotic plant invasions and increased atmospheric carbon dioxide (CO2) concentration have been determined to independently affect soil nematodes, a key component of soil biota. However, little is known about the long-term effects of these two global change factors and their interactive effects. Over three consecutive years, we cultivated invasive alien plant Xanthium strumarium and its two phylogenetically related natives under both ambient (aCO2) and elevated (eCO2) atmospheric CO2 concentrations, and determined the effects of the invader and natives on soil nematodes under different CO2 concentrations and the relevant mechanism. The abundance of total soil nematodes and that of the dominant trophic group (herbivores) were significantly affected by plant species and CO2 concentration, and these effects were dependent on the experimental duration, however, the Shannon-diversity of nematodes was not affected by these factors. Under aCO2, both invasive and native species significantly increased the total nematode abundance and that of the dominant trophic group with increasing experimental duration, and the amplitude of the increase was greater under the invader relative to the natives. The eCO2 increased total nematode abundance (second year) and that of the dominant trophic group (third year) under the invader, but not under the natives (or even decreased) with increasing experimental duration. Root litter had greater effects on soil nematode abundance than leaf litter and root exudates did. This study indicates that eCO2 would aggravate effects of invasive plants on soil nematodes by increasing abundance, and these effects would vary with the duration.